Evaluation the Effect of 805 nm Wavelength Diode Laser on Repair of Mandibular Bone Repair and Skin Incisions in Rabbits - Khalil, Rasha A.; Mahmood, Ali S. (Iraqi Journal of Laser, 2010)
The long healing time of bone after tooth extraction in order to construct artificial teeth is uncomfortable to the patient because of aesthetic or masticatory problems in addition to the daily visit to dental clinic. The objective of this study was to evaluate the effect of 805 nm diode laser with long time intervals on repair of bone and skin incisions in rabbits through biochemical, radiological and histological findings. Eighteen New-Zealand rabbits were undergone surgical operations to make a cavity in the bone of the lower jaw, the rabbits were divided into two groups:- Group A (control group) containing nine rabbits. Group B (lased group) containing nine rabbits in which two cavities were done, one on the right side and the other on the left side of the mandible. The cavities were subdivided into two groups according to the exposure time. Group B1 (the right side) which was underwent treatment with 805 nm continuous diode laser with output power of 900mW and exposure time of 5 min, every 72 h for two weeks. Group B2 (the left side) which was underwent treatment with 805 nm continuous diode laser with output power of 900mW and exposure time of 10 min, every 72 h for two weeks. The diode laser with a wavelength of 805 nm, power 900 mW and operating on continuous mode was applied directly over the site of the cavity according to the group. Radiological findings, histological and biochemical evaluations for both bone and skin were done for all groups after 7, 14 and 28 days of follow up. The histological results showed that there was a complete wound healing and bone repair at day 28 postoperatively in sub group B2 which is represented by the group treated with 805 nm diode laser with exposure time of 10 min, every 72 hours. In conclusion, the 805 nm continuous wave diode laser with power density of 1.79 W/cm2 and exposure time of 10 min, every 72 h for two weeks was beneficial to stimulate healing in bone and skin.